Effect of spacer and crossflow velocity on the critical flux of bidisperse suspensions in microfiltration - Tanudjaja, Henry Jonathan (2017)
Crossflow microfiltration is a popular application spanning various industries. Although the impacts on fouling of feed bidispersity, crossflow velocity (CFV) and spacer, all of which are present in practical operations, are known separately, the understanding of the interplay of these three factors on fouling is lacking. Accordingly, this study used the Direct Observation Through the Membrane (DOTM) technique to characterize the critical flux of monodisperse and bidisperse polystyrene particles in both the absence and presence of a spacer over a range of CFV values. The results indicate that (i) the combined effects of both bidispersity (dp=3 µm and 10 µm) and spacer gave the highest Jcrit values for the smaller particles throughout the CFV range investigated; (ii) bidispersity was more effective in enhancing Jcrit at a lower CFV, while the presence of a spacer was more effective at a higher CFV; (iii) a higher CFV diminished the enhancement induced by bidispersity more than that by the spacer; and (iv) comparisons between models and experimental data reveal that shear-induced diffusion models based on monodisperse particles are deficient for bidisperse mixtures, because they cannot allow for particle size segregation effects that occur in flowing mixed systems.